Cybernetyczne aspekty modeli przepływów ludnościowych w międzyregionalnej analizie popytu konsumpcyjnego - Mynarski, Stefan (Wydział Prawa i Administracji UAM, 1971)
As a means of grasping the changes in population due to natural movements and migration the author proposes a multifactorial matrix. It permits a description of the functional mechanism of the whole population system including the births and deaths of certain of its elements.
Cybernetic Aspects of a Model Migration Population in an Interregional Analysis of Consumption Demands